Pelatihan Komputer Untuk Meningkatkan Keterampilan Dalam Penggunaan Miscrosoft Word Bagi Pemuda Cot Muda Itam - Ismuhadi; Liza Ulfa; Khairun Septiyanda (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
Abstract Computer Training to Improve Skills in Using Microsoft Word was held in Cot Muda Itam Village, Peureulak District, East Aceh District. Participants who took part were 15 people who were village youths. The method in writing this article uses a qualitative approach with a qualitative descriptive model in the form of descriptive or describing research phenomena or facts as they are related to Microsoft Word training work programs. The Microsoft Word training in this work program has the following stages: 1) the first step is to prepare a laptop and introduce the village of Cot Muda Itam about Microsoft Word and what is in Microsoft Word 2) Training on the use of Microsoft Word is followed by the youth of the village of Cot Muda Itam with a total of 15 people, then they know how to type properly and correctly. 3) Furthermore, if you have mastered these initial steps, the next step is to create a table in Microsoft Word. 4) then after being able to create a table then proceed to the next stage, namely printing the file that has been created. 5) After being briefed on the youth of Cot Muda Itam village, after that they were given the freedom to access Microsoft Word with the provided laptops and computers, by conducting tests on what they had learned so that the success rate of this program could be known. This training was carried out for 8 days from 2-9 December 2022. This activity is Community Service for the 2022/2023 Odd semester.   Keywords: computer training, improving skills, microsoft word